Advanced devices & instrumentation - American Association for the Advancement of Science (American Association for the Advancement of Science (AAAS), 2020)
The mission of the journal is to publish high-impact breakthroughs at all levels of electronics and photonics, including at the device, system, and instrumentation levels. Investigations into novel ideas, methods, and techniques, as well as into novel uses of existing applications.
Keywords: Electronics : Periodicals; Photonics : Periodicals; Electronics; Photonics